Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/w15091753
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Climate Change and Land Use Impact on Streamflow in the Present and Future under CMIP6 Climate Scenarios for the Parvara Mula Basin, India

Abstract: Understanding the likely impacts of climate change (CC) and Land Use Land Cover (LULC) on water resources (WR) is critical for a water basin’s mitigation. The present study intends to quantify the impact of (CC) and (LULC) on the streamflow (SF) of the Parvara Mula Basin (PMB) using SWAT. The SWAT model was calibrated and validated using the SWAT Calibration Uncertainty Program (SWAT-CUP) for the two time periods (2003–2007 and 2013–2016) and (2008–2010 and 2017–2018), respectively. To evaluate the model’s per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The Kappa coefficient measures how much less error is produced by a classification procedure when compared to an entirely random classification. [ 82,83,84,85 ] indicated that a kappa value of < 40% is poor, 40%–55% is fair, 55%–70% is good, 70%–85% very good, and >85% excellent. Therefore, a confusion matrix has been computed to obtain the kappa index.…”
Section: Methodsmentioning
confidence: 99%
“…The Kappa coefficient measures how much less error is produced by a classification procedure when compared to an entirely random classification. [ 82,83,84,85 ] indicated that a kappa value of < 40% is poor, 40%–55% is fair, 55%–70% is good, 70%–85% very good, and >85% excellent. Therefore, a confusion matrix has been computed to obtain the kappa index.…”
Section: Methodsmentioning
confidence: 99%
“…Global studies, exemplified by (Gaur & Singh, 2023;Mohseni et al, 2023), highlight the significant influence of LULC changes on basin flow patterns, while (Jiménez-Navarro et al, 2021;Mohammed et al, 2018;Mohammed, Saiful Islam, et al, 2017;Mohseni et al, 2023;Mollel et al, 2023;Sun et al, 2022;Ullah et al, 2023;Yalcin, 2023) explore the impact of climate change on flow across diverse basins. Recent research combining climate change and LULC effects reveals a notable impact on river basin flow, predicting decreased dry period flow and increased wet season flow (Bal et al, 2021;Fields et al, 2021;Mohseni et al, 2023). Although specific studies for the Teesta basin are lacking, research in the broader Indian sub-continent, like that conducted by (Mohseni et al, 2023), underscores the substantial impact of LULC and climate change on future flow, indicating a significant increase in peak flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research combining climate change and LULC effects reveals a notable impact on river basin flow, predicting decreased dry period flow and increased wet season flow (Bal et al, 2021;Fields et al, 2021;Mohseni et al, 2023). Although specific studies for the Teesta basin are lacking, research in the broader Indian sub-continent, like that conducted by (Mohseni et al, 2023), underscores the substantial impact of LULC and climate change on future flow, indicating a significant increase in peak flow.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the importance of streamflow forecasting has gained significant recognition [14,15]. On the other hand, streamflow prediction plays a vital role in long-term water resources planning and management [16][17][18]. Streamflow predictions are based on climate models and scenarios, which provide insights into potential changes in streamflow patterns under different climate change scenarios [11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used the SWAT model to evaluate the consequences of changing the climate on streamflow and sediment load [22,29,30]. For example, Mohseni et al (2023) [18] used the SWAT model to evaluate the impact of climate change and land use change on streamflow over the Parvara Mula Basin, India. The findings of the study indicate an increase in streamflow for future periods.…”
Section: Introductionmentioning
confidence: 99%